The Distribution Mechanism of Subsidized Liquid Petroleum Gas in Sajad District West Kalimantan: An Investigation Based on Islamic Law - Zarul Arifin (Al-Manahij: Jurnal Kajian Hukum Islam, 2021)
This research is based on an initial survey of the distribution of subsidized 3-kg LPG which I think is not right on target because it is full of fraudulent practices. In distributing LPG, it was found that many rich people still buy subsidized 3-kg LPG. In fact, according to government regulations, 3-kg LPG is intended for the poor economic community or small business owners. The problem that is the focus of this research is how the mechanism for distributing 3-kg LPG is in Sajad Regency, and how is the law on selling 3-kg LPG for the rich when viewed according to Islamic law. To answer these questions, data collection techniques were carried out through observation and interviews. The results of this study are 1) the distribution of 3-kg LPG is not in accordance with government regulations, namely the distribution of LPG prioritizes people who can afford it above the official price, while the poor can only get a small part of the official government price/national subsidy price, so there are more stock for sale at more expensive than the official price. 2) If viewed from Islamic law, the distribution of 3-kg LPG is not in accordance with the sharia business method because it is carried out by ignoring government regulations, namely traders are considered to have broken an agreement with the government regarding price determination. In addition, this buying and selling practice also lacks supervision, no sanctions and no law enforcement to maintain subsidy prices so that many sellers dare to violate contracts with the government and violate government regulations.